ANALISIS KESIAPSIAGAAN RUMAH TANGGA KELURAHAN TUBO TERHADAP BANJIR LAHAR DINGIN DI SUNGAI TUGURARA TERNATE - Nasarudin Nasarudin; Suliamin Kasnar; Rahedin Suwo (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2019)
AbstractThe purpose of this study was to determine the preparedness of households residing on the banks of the Tugurara river against lahar flooding on aspects of knowledge related to lava flooding, information-seeking behavior about disasters, attitudes of vigilance, and community attitudes in dealing with disasters. Ternate community in facing the threat of cold lava flood in the Tugurara watershed. The method used is a survey method with a questionnaire targeting households that live on the banks of the Ternate Tugurara river. The results showed that household/community preparedness on the banks of the Tugurara watershed in the face of cold lava floods was not yet optimal. Household preparedness in the aspect of knowledge related to disasters 94.62% who do not have knowledge 5.38%. In the aspect of finding information related to household disasters that sometimes search for disaster, information reaches 36.2%. Whereas for household vigilance attitudes that often have a vigilance attitude towards the threat of danger the percentage reached 29.2% and those who rarely had vigilance attitudes were 24.6%. While the attitude of households who have an attitude in dealing with disasters that strongly agrees to the actions taken when a disaster occurs is 82.3% and the hesitant household is 2.3%.Keywords: Preparedness, Flood, Lava. AbstrakTujuan penelitian ini adalah mengetahui kesiapsiagaan rumah tangga yang bermukim di bantaran sungai Tugurara terhadap banjir lahar pada aspek pengetahuan terkait banjir lahar, perilaku pencarian informasi tentang bencana, sikap kewaspadaan ancaman bahaya, dan sikap masyarakat dalam menghadapi bencana. Ternate masyarakat dalam menghadapi ancaman banjir lahar dingin di DAS Tugurara. Metode yang digunakan adalah metode survei dengan kuesioner dengan sasaran pada rumah tangga yang bermukim di bantaran sungai Tugurara Ternate. Hasil penelitian menunjukkan bahwa kesiapsiagaan rumah tangga/masyarakat di bantaran DAS Tugurara dalam menghadapi banjir lahar dingin belum maksimal. Kesiapsiagaan rumah tangga pada aspek pengetahuan terkait bencana 94,62% yang tidak memiliki pengetahuan 5,38%. Pada aspek pencarian informasi terkait bencana rumah tangga yang kadang mencari informasi bencana mencapai 36,2%. Sedangkan pada sikap kewaspadaan rumah tangga yang sering memiliki sikap waspada terhadap ancaman bahaya persentase mencapai 29,2% dan yang jarang memiliki sikap kewaspadaan adalah 24,6%. Sedangkan sikap rumah tangga yang memiliki sikap dalam menghadapi bencana yang sangat setuju terhadap tindakan yang dilakukan pada saat terjadi bencana adalah 82,3% dan rumah tangga yang ragu-ragu adalah 2,3%. Kata kunci : Kesiapsiagaan, Banjir, Lahar.